Democratic model of the city's cultural landscape transformation - Stepanenko, Anastasiia (Ukrainian Cultural Studies, 2024)
Background. The analysis of the city's cultural landscape allows investigation of features and the context of local culture. The hybrid organization of the city as a media-architectural complex, and the involvement of city residents in the processes of making administrative decisions in various forms create a field for a democratic model of transformation of the cities' cultural landscapes. This model provides not just residents' free access to the city space but also their active participation in making decisions about its use and making changes. Methods. The methods of empirical analysis, systematization, generalization, and comparison of the obtained data, as well as the description of the obtained results, were used. Results. The cultural landscape of the city is the result of the interaction of various actors – local self-government, public organizations, enterprises, creative industries, and residents. Changes in politics, economy, and society can contribute to the development of new ideas and approaches to the cultural landscape of the city that reflect current needs and values. The democratic model of a city's cultural landscape development requires an effective communication system between all actors. The media play here a key role by shaping the perception, idea, and public opinion of urban space, and influencing decision-making in this domain. In the context of the studied model of the city's cultural landscape development, the media have an important task of ensuring openness and availability of information about various initiatives and projects implemented in the city. They help involve citizens in discussions, consultations, and public debates on city development issues, and promote the formation of common development goals and strategies. Conclusions. It was defined that the development of a democratic model of the city's cultural landscape transformation is important for ensuring sustainable urban development and improving the residents' quality of life. The media play an important role in creating an open and transparent urban environment that promotes the active participation of citizens in decision-making processes and shaping the city's cultural landscape. Their role is to ensure wide access to information, facilitate an open exchange of views and ideas, and support dialogue between all stakeholders in urban development. Local residents as social actors can make deep changes in the city's cultural landscape structure. This plays a positive role for local democracies and the culture of interaction because local actors are the most interested party when a local-level problem acquires a high level of complexity.
Keywords: city; cultural landscape of the city; transformation; social actors; media